2020
DOI: 10.1093/icvts/ivaa052
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cardiopulmonary bypass management on outcome: a propensity matched comparison between minimally invasive and conventional valve surgery

Abstract: Abstract OBJECTIVES Research concerning cardiopulmonary bypass (CPB) management during minimally invasive cardiac surgery (MICS) is scarce. We investigated the effect of CPB parameters such as pump flow, haemoglobin concentration and oxygen delivery on clinical outcome and renal function in a propensity matched comparison between MICS and median sternotomy (MS) for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…10 In this series, compared to CAVR, CPB and surgery times during MIAVR were prolonged by an average of 12 and 26 minutes, respectively. As already described by other groups, 15,18 these results did not seem to produce worse clinical outcomes. Although it is reasonable to conclude that a longer CPB time may influence outcomes, considering what extent of lengthening would be clinically significant is also always necessary.…”
Section: Discussionsupporting
confidence: 85%
“…10 In this series, compared to CAVR, CPB and surgery times during MIAVR were prolonged by an average of 12 and 26 minutes, respectively. As already described by other groups, 15,18 these results did not seem to produce worse clinical outcomes. Although it is reasonable to conclude that a longer CPB time may influence outcomes, considering what extent of lengthening would be clinically significant is also always necessary.…”
Section: Discussionsupporting
confidence: 85%
“…Using kidney function as the most robust organ function endpoint, our group recently demonstrated that an equivalent organ‐specific, as well as clinical outcome between MIVT and conventional MV surgery, is achievable through targeting a minimal oxygen delivery during the duration of cardiopulmonary bypass. However, to cope with the frequent inferences of intraoperative flow restrictions over a longer procedural time during MIVT, other means need to be applied as the tolerance of lower body temperature, the pursuit of a higher intra‐operative hematocrit level, and the use of blood preserving measures 21 . Moreover, operative times may probably be less decisive for patient outcomes, as long as they are not excessively long.…”
Section: Discussionmentioning
confidence: 99%
“…Using kidney function as most robust organ function endpoint, our group recently demonstrated that an equivalent organ-specific as well as clinical outcome between MIVT and conventional MV surgery is achievable through targeting an minimal oxygen delivery during the duration of cardiopulmonary bypass. However, in order to cope with the frequent inferences of intra-operative flow restrictions over a longer procedural time during MIVT, other means need to be applied as the tolerance of lower body temperature, the pursuit of a higher intra-operative hematocrit level and the use of blood preserving measures 21 . Moreover, operative times may probably be less decisive for patient outcomes, as long as they are not excessively long.…”
Section: Discussionmentioning
confidence: 99%